Предмет: Алгебра,
автор: polina5avina
Упростите выражение. a) 2*(x-3y)-3*(x+y) б) (3a-b)*(a+2b)-(2a-b)*(a-b)
Помогите срочно
Ответы
Автор ответа:
0
а)2(x-3y)-3(x+y) = 2x - 6y - 3x - 3y = - x - 9y б)(3a-b)(a +2b)-(2a-b)(a-b) = (3a^2 + 6ab - ab - 2b^2) - (2a^2 - 2ab - ab + b^2) = (3a^2 + 5ab - 2b^2) - (2a^2 - 3ab + b ^2) = 3a^2 + 5ab - 2b^2 - 2a^2 - 3ab + b^2 ...
Автор ответа:
0
2*(x-3y)-3*(x+y)=2x-6y-3x-3y=-x-9y
(3a-b)*(a+2b)-(2a-b)*(a-b)=3a^2+6ab-ab-2b^2-2a^2+2ab+ab+b^2=a^2+8ab-b^2
(3a-b)*(a+2b)-(2a-b)*(a-b)=3a^2+6ab-ab-2b^2-2a^2+2ab+ab+b^2=a^2+8ab-b^2
Похожие вопросы
Предмет: Обществознание,
автор: alinapopytova
Предмет: Обществознание,
автор: maiklpro
Предмет: Информатика,
автор: iliyaelizarof2004
Предмет: Математика,
автор: TANKIST20051
Предмет: Обществознание,
автор: снейк4